ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGAGENDAAN SURAT PADA UNIVERSITAS MUHAMMADIYAH JAMBI - H, Noneng Marthiawati.; Kurniawansyah, Kevin; Nugraha, Hafiz (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2022)
Computer-based information systems are needed, especially in the development of an organization, in this case is the University of Muhammadiyah Jambi. Where the University of Muhammadiyah Jambi pays less attention to incoming and outgoing letters because currently the mail scheduling information system has not been fully integrated with the system where for mail scheduling still uses the conventional system. Where the process is still carried out by separating incoming and outgoing letters and then writing or recording several parts of the letter, namely: letter number, letter description, letter origin, incoming letter date, outgoing letter date, agenda date, document. The purpose of this research is to analyze and design a prototype letter scheduling system so as to increase the effectiveness and efficiency in scheduling letters and speed up the process of searching for letters so as to make it easier for mail managers to find letters according to their needs. This design was made using the visual paradigm and using object-based modeling techniques to describe the analysis and design of the system, namely in the form of use case diagrams, class diagrams, and activity diagrams. This research resulted in a prototype design of an analysis system and design of a letter scheduling information system at the University of Muhammadiyah Jambi. On this basis, an integrated system is needed, it is hoped that the system can be implemented directly to increase the effectiveness and efficiency of the implementation of the letter logging information system at the University of Muhammadiyah Jambi.